International Law within the domestic legal system: The Malaysian perspective - Shuaib, Farid Sufian (2019)
The paper looks at the interaction between international law and domestic law in searching for unity of legal system. It looks from the perspective of the Malaysian legal system by examining cases decided by the Malaysian courts. The paper finds that there are inconsistencies in the case law and provides some observation as guidelines for the future.